Comparative study of mifepristone versus balloon catheter for cervical ripening and induction of labour in previous caesarean section - Dahiya, Krishna; Yadav, Nisha; Dahiya, Pushpa; Nandal, Isha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of this present study was to compare the efficacy of oral mifepristone and balloon catheter for cervical ripening and induction of labour in women with previous caesarean section. Methods: This prospective study was conducted on 130 pregnant women with previous 1 caesarean section and term singleton pregnancy admitted for induction of labour. Sixty-five patients were induced with oral mifepristone (Group 1) and in another 65 transcervical balloon catheter (Group 2) was inserted for induction of labour. Both groups were than compared with respect to change in bishop score, induction to active phase interval, induction to delivery interval, dose of oxytocin in milliunits, mode of delivery, maternal complication and fetal outcomes. Results: Change in bishop score after induction was more in mifepristone group than balloon catheter group (p=0.002). Favorable bishop score was more in Group 1 (83.07%) than Group 2 (66%), p=0.05. There was significant difference in mode of delivery between two groups, 61.53% in Group 1, and 32.3% in Group 2 delivered vaginally (p<0.001). Conclusions: Present study showed that mifepristone is an alternative to balloon catheter for induction of labour in women with previous one caesarean section with poor bishop score.